MSCs relieve SLE by modulation of Th17 cells through MMPs–CCL2–CCR2–IL‐17 pathway. Issue 1 (14th September 2021) - Jiang, Bo; Yao, Genhong; Tang, Xiaojun; Yang, Xi; Feng, Xuebing
Abstract: Objective: To explore the modulation of mesenchymal stem cells (MSCs) on T helper 17 (Th17) cells in systemic lupus erythematosus (SLE) and underlying mechanism. Methods: The concentration of matrix metalloproteinases (MMPs), CC chemokine ligand‐2 (CCL2), and interleukin‐17 (IL‐17) in the serum of SLE patients and mice were detected by enzyme‐linked immunosorbent assay. The expression of CCR2 and IL‐17 of T lymphocytes were determined by flow cytometry. The effects of MSCs on Th17 cells were analyzed in lupus mice and coculture system in vitro. Results: The levels of MMPs, CCL2, IL‐17, CCR2, and percentages of Th17 cells were significantly increased in SLE patients. These molecules and numbers of Th17 cells were downregulated by umbilical cord‐derived MSCs (UC‐MSCs) which relieve SLE disease. CCL2 neutralizing antibody blocked the effects of MSCs on Th17 cells. MMPs reversed the function of CCL2. Conclusion: The beneficial effects of MSCs on SLE patients rely on secreting MMPs, which reverse the activity of CCL2 to inhibit Th17 cells, suggesting the crucial MSCs–MMP–CCL2–CCR2–Th17–IL‐17 pathway in SLE. Highlights: CCL2 activates Th17 to participate in SLE. UC‐MSCs secret MMPs to hydrolyze CCL2. Hydrolyzed CCL2 inhibit Th17 to relieve SLE. Abstract : MSCs relieve SLE by MMPs‐CCL2‐Th17 pathway